한계고령화율(고령화의 한계기술대체율) 개념을 이용한 농촌지역 경제-복지의보완관계 모색 연구 - 박길환 (한국농촌경제연구원, 2015)
Concerning accelerated rural population aging, this article introduces the concept of the marginal rate of population aging (MRPA) drawing on the economics and welfare literatures. It is defined as the marginal rate of technical substitution between aggregate capital and “aging” aggregate labor. The traditional approach to (rural or agricultural) production was based on the presumption that aging does not affect production. However, the physical and mental capability of working decreases as population becomes aged. The externality of this declining capability needs to be reflected in aggregate productions and to be treated more significantly as population becomes more aged. After a review of the trends and spatial distributions of aging in Korea, a rural town is selected in this study as a case area whose parcel-level spatial data is analyzable in terms of MRPA. This exploratory analysis is focused on whether rural economic and social welfare may become complementary in rural aggregate production with MRPA if a design of the lifetime mortgage of farming assets (LMFA) leads to large-scale production and welfare improvements.
Keywords: 한계고령화율; 농촌경제후생; 농촌사회복지; 대규모 생산; marginal rate of population aging; MRPA; rural economic welfare; rural social welfare; large-scale production